Strategi Pembelajaran Kosa Kata Bahasa Arab di Kalangan Santri Pondok Pesantren Darul Kholidin - Muhamad Afiz Al-Farizi; Waki Ats Tsaqofi; Darsita Suparno; Muhammad Anas; Muhammad Zacky; Karlina Helmanita (Nawadeepa: Jurnal Pengabdian Masyarakat, 2026)
This study aims to describe the strategies of teaching Arabic vocabulary among eleventh-grade students at Darul Kholidin Islamic Boarding School, Bogor. Vocabulary (mufradāt) is a crucial component in Arabic language learning, as mastery of vocabulary facilitates comprehension of texts, sentence construction, and communication. This research employed a descriptive qualitative approach, involving observation, interviews, and documentation. The subjects of the study consisted of 25 purposively selected students who were actively engaged in Arabic language classes. The findings reveal that teachers implemented several strategies, including the direct method with an emphasis on speaking practice, language games, the use of visual media, repetition and memorization, as well as contextual learning linked to students’ daily activities in the boarding school. These strategies effectively enhanced students’ motivation, participation, and retention of new vocabulary. However, challenges were identified, such as limited learning time, varying levels of students’ abilities, and the lack of diverse learning media. The study suggests that innovative and contextual vocabulary teaching strategies are essential to improve Arabic language learning in Islamic boarding schools.